2016
DOI: 10.1080/02699052.2016.1219055
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of comorbidity trajectories associated with traumatic brain injury in veterans of the Iraq and Afghanistan wars

Abstract: It was found that TBI was most common in PCT-related trajectories, indicating that TBI is commonly comorbid with pain and mental health conditions for both men and women. The relatively young age of this cohort raises important questions regarding how disease burden, including the possibility of neurodegenerative sequelae, will accrue alongside normal age-related decline in individuals with TBI. Additional 'big data' methods and a longer observation period may allow the development of predictive models to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…However, higher levels of care coordination may be warranted due to greater healthcare need (e.g., multiple comorbidities, advanced or more severe conditions), limited personal resources, and frequent cross-system use. 7,[21][22][23] In addition to PACT, VA Office of Community Care has developed a triage tool to differentiate Veterans with low, moderate, or high needs for coordination to facilitate coordination and navigation within and outside the VA. This tool also helps in documenting the intensity ("dosage") of coordination delivered.…”
Section: Identifying Veterans Who Benefit Most From Care Coordinationmentioning
confidence: 99%
“…However, higher levels of care coordination may be warranted due to greater healthcare need (e.g., multiple comorbidities, advanced or more severe conditions), limited personal resources, and frequent cross-system use. 7,[21][22][23] In addition to PACT, VA Office of Community Care has developed a triage tool to differentiate Veterans with low, moderate, or high needs for coordination to facilitate coordination and navigation within and outside the VA. This tool also helps in documenting the intensity ("dosage") of coordination delivered.…”
Section: Identifying Veterans Who Benefit Most From Care Coordinationmentioning
confidence: 99%
“…TBI was most common in the PCT trajectory for both men and women. Women in the mental health and PCT trajectories were more likely than men to be diagnosed with depression …”
Section: Resultsmentioning
confidence: 88%
“…Women in the mental health and PCT trajectories were more likely than men to be diagnosed with depression. 32 Interpersonal Violence Iverson and Pogoda found that 18.8% of their allfemale sample (n = 176) reported a history of TBI from IPV in a cross-sectional survey by mail. Women with IPVrelated TBI reported poorer mental and physical health than women with no head injury.…”
Section: Comorbidity Phenotypesmentioning
confidence: 99%
“…In terms of chronic pain, female veterans are more likely to report headache and depression following TBI, whereas male veterans are more likely to report low-back pain after the injury. 61 Although the inciting event of TBI may be a purely mechanical injury leading to structural damage, significant morbidity following the trauma stems from psychological or psychiatric sequelae. It has been found that female veterans have a higher incidence of posttraumatic stress disorders (PTSDs) independent of TBI.…”
Section: Tbi In Female Veteransmentioning
confidence: 99%
“…In contrast, the only significant risk factor for unemployment among female veterans included in this study was the presence of affective or cognitive symptoms. 2 Other potential barriers to successful integration back into civilian society specific to men include a significantly higher risk of developing a comorbid substance use disorder 27,61 and dementia following the injury. 71 This suggests that male and female veterans may need different, targeted resources to facilitate employment.…”
Section: Tbi In Male Veteransmentioning
confidence: 99%